Classificação de madeira maciça para estruturas. - Cruz, H. (2009)
Submitted by Paulo Frazão (pfrazao@lnec.pt) on 2009-10-14T13:28:26Z No. of bitstreams: 1 CM 24 ROSTO.pdf: 586593 bytes, checksum: 08095aeb5c5653b19cf5059759343235 (MD5)